2014
DOI: 10.3138/ptc.2013-45
|View full text |Cite
|
Sign up to set email alerts
|

Reliability and Validity of Two Versions of the Upper Extremity Functional Index

Abstract: Purpose: To examine the reliability, validity, and sensitivity to change of the 20-item version and the Rasch-refined 15-item version of the Upper Extremity Functional Index (UEFI-20 and UEFI-15, respectively) and to determine the impact of arm dominance on the positive minimal clinically important difference (pMCID). Methods: Adults with upper-extremity (UE) dysfunction completed the UEFI-20, Upper Extremity Functional Scale (UEFS), Pain Limitation Scale, and Pain Intensity Scale at their initial physiotherap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
51
1
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(58 citation statements)
references
References 31 publications
4
51
1
2
Order By: Relevance
“…The degree of differentiation of the tumor was evaluated according to the classification of tumors from the World Health Organization (WHO); accordingly, the tumors were categorized into undifferentiated, poorly differentiated, moderately differentiated, and well differentiated tumors. The pathological diagnosis [20] was confirmed by two senior pathologists.…”
Section: Methodsmentioning
confidence: 99%
“…The degree of differentiation of the tumor was evaluated according to the classification of tumors from the World Health Organization (WHO); accordingly, the tumors were categorized into undifferentiated, poorly differentiated, moderately differentiated, and well differentiated tumors. The pathological diagnosis [20] was confirmed by two senior pathologists.…”
Section: Methodsmentioning
confidence: 99%
“…It has been tested in general populations and generates scores for physical function, and the impact of physical limitations on daily life [45, 49]. The UEFI 15 is a validated patient reported measure for adults with upper extremity dysfunction [46, 47]. The FDI physical score is a short 5 item questionnaire that assesses the physical impact of facial weakness [48].…”
Section: Methodsmentioning
confidence: 99%
“…Hefford further established the reliability, validity, and responsiveness of the PSFS with upper extremity dysfunction [9]. Chesworth found that the UEFI was a reliable measure (Intraclass correlation coefficient (ICC)=0.94) [10]. The MCID for the UEFI was found to be between 6-7 depending on which version of the UEFI was used.…”
Section: Case Presentationmentioning
confidence: 99%